The Crises and Agony of International Development Cooperation: Consequences for Brazilian Foreign Policy - Pietro Carlos de Souza Rodrigues; Patrícia Andrade de Oliveira e Silva (Contexto Internacional)
Abstract At the beginning of this century, International Development Cooperation (IDC) began to occupy a central position in Brazil’s international status. Political and social transformations created conditions for Brazil to begin acting as a relevant protagonist in international projects, especially in developing nations, through South-South Cooperation (SSC). However, a succession of crises after 2011 and the emergence of ideas opposed to cooperation during the Bolsonaro administration (2019-2022) altered the conditions that sustained IDC as part of Brazilian foreign policy. In this article, we will identify the political and economic conditions that ensured (1) the structuring and (2) the growth of Brazilian cooperation up until 2011, and we will argue that the loss of these conditions resulted in IDC’s (3) decline, leading to (4) its agony beginning in 2019. Finally, we will evaluate several consequences of the cooperation crisis based on an evaluation of Brazilian foreign policy in the global health agenda, and its commercial relationship with African nations.